2011
DOI: 10.1007/s00419-011-0569-1
|View full text |Cite
|
Sign up to set email alerts
|

The creep behavior of simple structures with a stress range-dependent constitutive model

Abstract: This version is available at https://strathprints.strath.ac.uk/37093/ Strathprints is designed to allow users to access the research output of the University of Strathclyde. Unless otherwise explicitly stated on the manuscript, Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Please check the manuscript for details of any other licences that may have been applied. You may not engage in further distribution of the material for any pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…This result may seem surprising at first. In reference [22], it is shown in a study of a beam in bending and a pressurized thick cylinder that, for load-controlled steady creep and values of maximum elastic stress 50 per cent above the transition stress in the modified power-law, the pure power-law solution does dominate as expected. However, this is apparently not the case for stress relaxation (at least in the present simple example).…”
Section: Effect Of the Modified Power-law On Stress Relaxationmentioning
confidence: 69%
See 2 more Smart Citations
“…This result may seem surprising at first. In reference [22], it is shown in a study of a beam in bending and a pressurized thick cylinder that, for load-controlled steady creep and values of maximum elastic stress 50 per cent above the transition stress in the modified power-law, the pure power-law solution does dominate as expected. However, this is apparently not the case for stress relaxation (at least in the present simple example).…”
Section: Effect Of the Modified Power-law On Stress Relaxationmentioning
confidence: 69%
“…10 Equivalent stress-strain trajectories for the evaluation point of Y-piece from ABAQUS FEA with pure power-law creep Fig. 11 Equivalent stress-strain trajectories for evaluation point of Y-piece from ABAQUS FEA with modified power-law creep in Section 3 and it is seen that the linear viscous part of the modified power-law has a significant effect in stress relaxation, more so than what is observed for constant load steady creep [16,22]. The simple twobar structure [4] has long been used as a reference benchmark in studies of elastic follow-up [4][5][6][7][8][9][10]: assuming a creep law based on power-law secondary creep alone, it can be shown that this structure has a stress-strain trajectory which is indeed independent of the power index.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Such processes include creep, stress relaxation, long-term strength, elastic lag, etc. (Grimstad et al, 2010;Yin and Tong, 2011;Boyle, 2012;Zhao et al, 2017a,b), among which the creep behavior of the soil is the most extensive research topic. Excessive creep in the soil can lead to differential settlement in buildings, dam foundation failures, and landslides.…”
Section: Introductionmentioning
confidence: 99%
“…For example, creep over a range of stress does not follow one simple power law relationship and typically exhibits one power law at low stress and another at high stress—a phenomenon known as power law breakdown. 16 To capture this behavior, stress range dependent response functions 1720 or constitutive models with several internal state variables 21,22 are developed. To calibrate such models, many experimental data and advanced identification methods are required.…”
Section: Introductionmentioning
confidence: 99%